A superior vena cava to right pulmonary artery shunt for severe right ventricular outflow tract stenosis caused by an unresectable cardiac tumor. Issue 3 (March 2020) - Tsuji, Shigeto; Nawata, Kan; Shimada, Shogo; Hirata, Yasutaka; Ono, Minoru
Abstract: We report the case of a 47-year-old man who was diagnosed with severe right ventricular outflow tract (RVOT) stenosis due to a space-occupying lesion; the diagnosis was made using computed tomography. He underwent mass reduction, pulmonary valve replacement, and RVOT reconstruction with a bovine pericardial patch. The pathological diagnosis was undifferentiated pleomorphic sarcoma originating from the myocardium. As the mass resection was incomplete, he received heavy particle therapy. He did not want to receive adjuvant chemotherapy. Four months later, severe RVOT stenosis recurred because the residual mass had invaded the prosthetic valve in the pulmonic position and one of the cusps was fixed in the closed position. He presented with dyspnea and marked lower leg edema. We performed superior vena cava (SVC) to right pulmonary artery (RPA) shunting as a palliative operation to improve his heart failure symptoms. After surgery, his symptoms improved; his hemodynamics have been stable for one year. SVC-RPA shunting is a palliative operation but can be used to effectively treat severe RVOT stenosis caused by unresectable cardiac tumors. <Learning objective: Malignant primary cardiac tumors commonly recur after complete surgical resection and they have the potential to obstruct intracardiac blood flow. The superior vena cava to right pulmonary artery shunt may be useful for treating right ventricular outflow tract stenosis due to unresectable cardiac tumors.>